Development Peculiarities for Agrophyto-cenosis of Spring Barley (Hordeum vulgare L.) subject to the Fertilization System and Whether Conditions - О. В. Телепенько (Plant Varieties Studying and Protection)
Analyzed has been conducted on parameters of productivity and efficiency increase for Helios and Comandor varieties of spring barley (Hordeum vulgare L.) on fertilized NPK background after soya as a forecrop.